2022
DOI: 10.1038/s41586-022-04516-4
|View full text |Cite|
|
Sign up to set email alerts
|

Catalytic synthesis of phenols with nitrous oxide

Abstract: The development of catalytic chemical processes that enable the revalorization of nitrous oxide (N2O) is an attractive strategy to alleviate the environmental threat posed by its emissions1–6. Traditionally, N2O has been considered an inert molecule, intractable for organic chemists as an oxidant or O-atom transfer reagent, owing to the harsh conditions required for its activation (>150 °C, 50‒200 bar)7–11. Here we report an insertion of N2O into a Ni‒C bond under mild conditions (room temperature, 1.5–2 ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 43 publications
1
49
0
Order By: Relevance
“…A wide array of benzoic acids with various substituents and heterocycles were transformed into phenols under optimized conditions. When they carry weak electron-donating groups including alkyl substituents (12−15), strong electron-donating groups including −OMe at the meta position (16) and −OPh at the para position (17), and two alkyl ether substituents at the ortho and meta positions (18), these benzoic acids could be converted into the corresponding phenols efficiently (Figure 3a). To reveal the practicality, the reactions can be scaled up to the gram scale (12 mmol scale) without affecting the reaction efficiency (12)(13)(14)17).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wide array of benzoic acids with various substituents and heterocycles were transformed into phenols under optimized conditions. When they carry weak electron-donating groups including alkyl substituents (12−15), strong electron-donating groups including −OMe at the meta position (16) and −OPh at the para position (17), and two alkyl ether substituents at the ortho and meta positions (18), these benzoic acids could be converted into the corresponding phenols efficiently (Figure 3a). To reveal the practicality, the reactions can be scaled up to the gram scale (12 mmol scale) without affecting the reaction efficiency (12)(13)(14)17).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Using GC-MS, the formation of CO 2 was confirmed in the model reaction (Figure 7d). When 18 O-labeled benzoic acid was employed as the starting material, careful analysis of the isotope distribution in the products revealed that the 18 O isotope only exists in CO 2 and the ester product only contains the regular 16 O atom (Figure 7e). This isotope labeling experiment suggests that the oxygen atom in the final phenol product is from m-CPBA instead of benzoic acid.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 As recent important progress, it is reported that the insertion of N 2 O into a Ni–C bond of the Ni catalyst enabled to deliver phenols with benign N 2 even at room temperature and 1.5–2 bar of N 2 O conditions. 40…”
Section: Resultsmentioning
confidence: 99%
“…38,39 As recent important progress, it is reported that the insertion of N 2 O into a Ni-C bond of the Ni catalyst enabled to deliver phenols with benign N 2 even at room temperature and 1.5-2 bar of N 2 O conditions. 40 N 2 O has also been found to be equally important in homogeneous solution chemistry, including selective oxidation of highly reactive compounds such as disilenes or low-valent metallocenes and the synthesis of complex organometallic molecules as nitrogen donors. 41 These potential revenues from N 2 O and the possible high conversion rate of N 2 O into NO x seem to be positive evidence for continuing to develop this ammonia synthesis based on N 2 /H 2 O plasma to a further matured level of a green alternative and/or a complement process to the H-B process in the near future.…”
Section: Resultsmentioning
confidence: 99%